Faktor-Faktor yang Berhubungan dengan Kejadian Baby Blues Syndrome pada Ibu Postpartum di Wilayah Kerja Puskesmas Teling Manado - Dwi Winarsih; Silvia D. Mayasari Riu; Irma M. Yahya (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
Baby blues syndrome occurs in mothers after giving birth, which has an impact on both the mother and the baby. Many factors cause baby blues such as lack of mental preparation to become a mother due to young age and inexperience, the number of children a mother has causes susceptibility to suffer from baby blues. The purpose of this research was to find out the factors related to the occurrence of baby blues syndrome at the Teling Community Health Center Of Manado. This type of research is observational analytic with a cross-sectional approach. The sampling technique used simple random sampling with a total of 59 respondents. Data were collected using the Edinburgh Postpartum Depression Scale (EPDS) questionnaire. The collected data were processed with the help of the SPSS computer program, data analysis with the Chi Square Test with a significance level of α 0.05. The results of the study showed that there was a correlation between age and Blues Syndrome at the Teling Community Health Center (P value 0.000 < α 0.05). There was a correlation between parity and Blues Syndrome at the Teling Manado Community Health Center (P value 0.008 < α 0.05). The conclusion of this study is that there is a correlation between age and parity with Blues Syndrome at the Teling Health Center. It is suggested to nurses as caregivers to not only meet physical needs but also psychological needs, especially identifying abnormal deviations as early as possible and collaborating with other health teams in meeting emotional needs through providing counseling, bonding attachment between mothers and their babies during the postpartum period so that mothers get good health and healthy babies.